Evaluation of roughage inclusion rate within a total mixed ration effects on feedlot performance, carcass characteristics, and fatty acid composition of subcutaneous adipose, intramuscular adipose, and muscle tissue of Wagyu cattle - Linton, Kathryn, author; Peel, Kraig, advisor; Archibeque, Shawn, committee member; Holt, Timothy, committee member (Colorado State University. Libraries, 2015)
The objective of this study was to investigate the effect of roughage inclusion rate of 10, 20, and 30% within a total mixed ration on feedlot performance, carcass composition and marbling distribution in Wagyu cattle (n=41). Upon arrival, cattle were acclimated to bunk style feeding. Initial body weights were collected. Animals were blocked by sex and weight to be assigned to 1 of 3 roughage inclusion rate treatments. Treatments included 1) 10% roughage inclusion on dry matter basis; 2) 20% roughage inclusion and 3) 30% roughage inclusion on dry matter basis. Diets were formulated to be isoenergentic, isonitrogenous, and isoamylolytic. Animals were weighed every 7d. For harvest animals were transported to a commercial abattoir. Hot carcass weight (HCW) was determined at time of harvest, intramuscular adipose, and subcutaneous adipose tissue was collected at harvest and snap frozen for analysis of FA composition. Longissimus muscle area (LMA) and backfat (BF) carcass measurements were determined after 21d storage at 0° C chill. A 1.25 cm cross section of longissimus dorsi at 12th and 13th rib interface was collected for Computer Vision System Ribeye Camera evaluation of marbling distribution. Limited treatment effects were observed. Feedlot performance and carcass characteristics were not significantly affected by roughage inclusion rate (P>0.05). Treatment presented a significant effect on Linoleic acid (C18:3) concentration within the longissimus muscle tissue (P=0.05). Concentration of C18:3 increased with increased roughage inclusion rate. Fatty acid profiles for LM, IMF and SQ tissues were similar across treatments. There was not treatment effect for marbling distribution collected via Computer Vision System Ribeye Camera evaluation. Overall, the data suggests that roughage inclusion rate causes very little impact on feedlot performance, carcass characteristics, fatty acid composition and marbling distribution in Wagyu cattle.
Keywords: fatty acid composition; feedlot performance; marbling distribution; roughage inclusion; Wagyu